2008
DOI: 10.1038/sj.bjc.6604730
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced killing of androgen-independent prostate cancer cells using inositol hexakisphosphate in combination with proteasome inhibitors

Abstract: Effective treatments for androgen-independent prostate cancer (AIPCa) are lacking. To address this, emerging therapeutics such as proteasome inhibitors are currently undergoing clinical trials. Inositol hexakisphosphate (IP6) is an orally non-toxic phytochemical that exhibits antitumour activity against several types of cancer including PCa. We have previously shown that treatment of PC3 cells with IP6 induces the transcription of a subset of nuclear factor-kB (NF-kB)-responsive and pro-apoptotic BCL-2 family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Treatment with DNMT1 inhibitors and HDAC inhibitors which activate Bik expression from the endogenous (silenced) Bik locus and the use of proteasomal inhibitors that stabilize BIK protein (in addition to other BH3-only members such as BIM and NOXA) appear to be highly promising anticancer approaches. The efficacy of proteasome inhibitors was also reported to be enhanced in combination with other chemotherapeutic agents such as TRAIL (Nikrad et al, 2005; Zhu et al, 2005a), cisplatin (Li et al, 2008) and inositol hexakisphosphate (Diallo et al, 2008). …”
Section: Bik and Human Cancermentioning
confidence: 99%
“…Treatment with DNMT1 inhibitors and HDAC inhibitors which activate Bik expression from the endogenous (silenced) Bik locus and the use of proteasomal inhibitors that stabilize BIK protein (in addition to other BH3-only members such as BIM and NOXA) appear to be highly promising anticancer approaches. The efficacy of proteasome inhibitors was also reported to be enhanced in combination with other chemotherapeutic agents such as TRAIL (Nikrad et al, 2005; Zhu et al, 2005a), cisplatin (Li et al, 2008) and inositol hexakisphosphate (Diallo et al, 2008). …”
Section: Bik and Human Cancermentioning
confidence: 99%
“…It has been reported that pharmacological inhibition of the proteasome was associated with alterations in protein expression profile of cardiomyocyte, and modulated cardiovascular disease progression [12,13]. MG132, a specific proteasome inhibitor, has been shown to suppress proliferation and inflammation [14], and possess proapoptotic [15,16] and antineoplastic [17,18] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby the question is still open and further studies are warranted to understand whether p53 activity is effectively required in mediating anticancer effects displayed by both InsP6 and myo-Ins. Downstream of p53 InsP6 has been demonstrated to reduce prosurvival factors and to upregulate caspases and other components of the proapoptotic BCL-2 family [ 63 66 ]. Furthermore, InsP6 has been shown to inhibit NF-kB activity in different cancers [ 67 , 68 ].…”
Section: Molecular Mechanisms Of Actionmentioning
confidence: 99%